Single-molecule long-read sequencing facilitates shrimp transcriptome research. Issue 1 (December 2018) - Zeng, Digang; Chen, Xiuli; Peng, Jinxia; Yang, Chunling; Peng, Min; Zhu, Weilin; Xie, Daxiang; He, Pingping; Wei, Pinyuan; Lin, Yong; Zhao, Yongzhen; Chen, Xiaohan
Abstract Although shrimp are of great economic importance, few full-length shrimp transcriptomes are available. Here, we used Pacific Biosciences single-molecule real-time (SMRT) long-read sequencing technology to generate transcripts from the Pacific white shrimp (Litopenaeus vannamei ). We obtained 322, 600 full-length non-chimeric reads, from which we generated 51, 367 high-quality unique full-length transcripts. We corrected errors in the SMRT sequences by comparison with Illumina-produced short reads. We successfully annotated 81.72% of all unique SMRT transcripts against the NCBI non-redundant database, 58.63% against Swiss-Prot, 45.38% against Gene Ontology, 32.57% against Clusters of Orthologous Groups of proteins (COG), and 47.83% against Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Across all transcripts, we identified 3, 958 long non-coding RNAs (lncRNAs) and 80, 650 simple sequence repeats (SSRs). Our study provides a rich set of full-length cDNA sequences forL. vannamei, which will greatly facilitate shrimp transcriptome research.